2016
DOI: 10.18632/oncotarget.12085
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of pemetrexed-induced inhibition of thymidylate synthase in non-small cell lung cancer with FLT-PET imaging

Abstract: Inhibition of thymidylate synthase (TS) results in a transient flare in DNA thymidine salvage pathway activity measurable with FLT ([18F]thymidine)-positron emission tomography (PET). Here we characterize this imaging strategy for potential clinical translation in non-small cell lung cancer (NSCLC). Since pemetrexed acts by inhibiting TS, we defined the kinetics of increases in thymidine salvage pathway mediated by TS inhibition following treatment with pemetrexed in vitro. Next, using a mouse model of NSCLC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…As a result, this drug-induced compensatory “flare” in thymidine salvage pathway activity is an indicator of successful TS inhibition. This drug-induced change in tumor metabolism can be made visible through 18 F-thymidine (FLT)-positron emission tomography (PET)[ 2 , 5 7 ], an analog of thymidine. FLT, first described by Shields in 1998 [ 8 ], is an investigational imaging biomarker of the thymidine salvage pathway currently in use for human clinical trials primarily as a validated surrogate marker of tumor proliferation [ 9 – 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, this drug-induced compensatory “flare” in thymidine salvage pathway activity is an indicator of successful TS inhibition. This drug-induced change in tumor metabolism can be made visible through 18 F-thymidine (FLT)-positron emission tomography (PET)[ 2 , 5 7 ], an analog of thymidine. FLT, first described by Shields in 1998 [ 8 ], is an investigational imaging biomarker of the thymidine salvage pathway currently in use for human clinical trials primarily as a validated surrogate marker of tumor proliferation [ 9 – 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our recent publication [ 7 ], we characterized the kinetics of the pemetrexed-induced thymidine salvage pathway “flare” in a xenograft mouse model of human NSCLC and demonstrated that the peak of the pemetrexed-induced thymidine salvage pathway “flare” consistently occurs at 2 hours of exposure to therapy both in vitro and in vivo . Beyond that 2 hour time point, the pemetrexed-induced “flare” signal decays, dissipating entirely by 24 hours of therapy at which time the anti-proliferative effects of successful therapy have begun to dominate thymidine salvage pathway activity.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the change in the post therapy PET avidity for responding tumors imaged with [ 11 C]thymidine was larger than what was observed with FDG PET imaging . Subsequent studies with the more clinically practical agent, [ 18 F]fluorothymidine (FLT), had demonstrated the ability to measure early response to chemotherapy for breast cancer, lung cancer, lymphoma, leukemia and other cancers. In addition, FLT PET can measure early response to targeted agents such as gefitinib for lung cancer and sunitinib for renal cell cancer .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to serving as a marker of changes in cellular proliferation, FLT may be able to serve in other capacities for assessing cancer response to therapy. For example, there is literature to support that imaging with thymidine analogs, in particular FLT PET, has a potential imaging biomarker of effective therapeutic inhibition of thymidylate synthase (TS) a common cancer therapeutic target . TS is a rate‐limiting step in the de novo synthesis pathway, a parallel pathway that works in concert with the thymidine salvage pathway to source thymidine to the dividing cell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation